Pretreatment of rice straw using microwave assisted FeCl3-H3PO4 system for ethanol and oligosaccharides generation. (September 2019) - Kumar, Bikash; Bhardwaj, Nisha; Verma, Pradeep
Abstract: In this study, Box–Behnken design Response Surface Methodology (BBD-RSM) was used to develop microwave-assisted pretreatment (MAP) for Rice Straw (RS) using FeCl3 -H3 PO4 system. The concentration of FeCl3 and H3 PO4, pretreatment temperature and time was used as independent variables and complex severity considering the effect of all variables were also calculated. Based on BBD-RSM, 57.5% of sugar yield per biomass was obtained for pretreated (MAP) RS using FeCl3 (0.35 M), H3 PO4 (3%), pretreatment temperature and time of 155 °C and 10 min respectively with intermediate complex severity of 3.0. Based on the structural analysis using FTIR and XRD, it was suggested that the pretreatment results in reduction of crystallinity of RS that result in high crystallinity index (CrI) of 49.9% for efficient hydrolysis. Simultaneous saccharification and fermentation (SSF) of pretreated (MAP) RS resulted in maximum ethanol production of 7.0% (v/v) using in-house cellulase and Saccharomyces cerevisiae MTCC-173. The hydrolysis of pretreated (MAP) RS pulp using in-house produced endoxylanase resulted in generation of oligosaccharides. Highlights: Statistical method to optimize Microwave-assisted FeCl3 -H3 PO4 treatment of rice straw Fermentation of pretreated rice straw resulted in 7.0% ethanol production Hydrolysis of pretreated rice straw resulted in the generation of oligosaccharides